A new approach in patient QA: Beam delivery check and in-vivo dosimetry during radiotherapy treatment. (September 2016) - Talamonti, C.; Arilli, C.; Marrazzo, L.; Calusi, S.; Galeotti, C.; Wandel, Y.; Meattini, I.; Scoccianti, S.; Pallotta, S.
Abstract : Introduction: The development of complex radiotherapy techniques, together with the huge workload of linacs, requires comprehensive QA programs and the development of detectors and softwares allowing for reliable checks of the treatment delivery. Purpose: The aim of this work was to study the impact in patient QA of the use of the Integral Quality Monitoring (IQM) device (iRTSystems) and the portal imaging with the software SoftDiso (Best Medical) to verify the safe and accurate delivery of the prescribed dose. Materials & methods: The Anderson-Rando phantom was modified to mimic a female torso by adding two silicon gel breast implants. Standard conformal breast plans were calculated and the large area ionization chamber IQM was mounted on the accelerator gantry. PI acquired during treatments were used for in-vivo dose measurements using SoftDiso. Small errors induced on plans simulated deviation due to delivery problems and/or wrong positioning of the phantom. Results: Tests showed good performances of the combined use of the devices to detect errors, which could not be highlighted during the pre-treatment QA. There's correlation between two systems when errors due to small changes in delivered MU are induced. IQM can detect errors when field dimensions are changed of few millimetres while SoftDiso cannot, but is able to detect discrepancy on dose reconstruction with a precision of 5%. Conclusions: In the clinical practice these devices can play an important role in meeting the needs of modern and upcoming radiotherapy QA, and it allows checking the correct functioning of all components in the radiotherapy chain.